Apology: Its Nature and Patterns - Rio Rini Diah Moehkardi (Humaniora, 1997)
This paper is an outline of what apology is. Examples from English and Bahasa Indonesia -mostly taken from a study carried out among Australian and Indonesian undergraduate students in Canberra University (Moehkardi, 1993) are given in order to have a clearer picture of the realization of apologizing. It will focus on the discourse situations which usually calls for apology of which realization does not only deal with utterances but also with the notion of face. It is also necessary to bear in mind the need of understanding the semantic formulas "word, phrase or sentence which meets a particular semantic criterion or strategy, and anyone or more of these can be used to perform the act in question" (Fraser, 1980 in Wolfson and Judd, 1983:20) that would be appropriate in performing apology, especially in the setting of thetwo languages mentioned above.